DEVELOPMENT OF DIGITAL-BASED DIAGNOSTIC TESTS AS A TRIGGER FOR DIFFERENTIATED LEARNING IN THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM - Ahmad Habibi; Sri Subarinah; A.A. Sukarso; Muh. Makhrus; Ida Ermiana (RADJA PUBLIKA, 2026)
This study aims to develop a valid, practical, and effective digital-based diagnostic test to support differentiated learning in the Independent Curriculum. The method used was Research and Development (R&D) through stages of development, expert validation, limited trials, and large-scale trials. The results showed that the digital diagnostic test has a very high level of validity based on expert assessments of content, construction, and language aspects. In terms of practicality, teacher responses were in the very good category with a percentage of 89.38%, indicating that the instrument is easy to use and can accelerate the assessment process and result processing. In terms of effectiveness, there was an increase in student learning outcomes, indicated by an increase in the average score from 82.29 to 89.90. In addition, the test was able to identify student learning readiness as a basis for designing differentiated learning. Thus, the digital-based diagnostic test was declared valid, practical, and effective in improving the quality of learning and student learning outcomes.